Biographical dictionary of new Chinese entrepreneurs and business leaders - Zhang, Wenxian; Alon, Ilan (Edward Elgar, 2011)
This invaluable dictionary is the result of collaborative efforts across the globe. Over forty scholars from the United States, mainland China and Taiwan, United Kingdom, Germany, France, Norway, Israel and Malaysia contributed. They cover the full spectrum of Chinese industries from banking, finance and investment, real estate, transportation and infrastructure, to manufacturing, telecommunications, media, agriculture, automobile, pharmaceutical, food, trade, service and retail industries.